ANALISIS PENGARUH KEPRIBADIAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN DIMEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA PDAM TIRTO PANGURIPAN KABUPATEN KENDAL ) (Students' Journal of Economic and Management, 2013)
The study intended to test and the Influence of Personality and Job Characteristics on Employees Performance With Organizational Commitment Mediated (Studies in PDAM Tirto Panguripan Kabupaten Kendal). The population of this study were all employees of PDAM Tirto Panguripan Kendal, amounting to 115 people. Using census sampling method, which all members of the population being sampled, so the sample size is 115 respondents. The results prove that the model's ability to correctly describe the relationship personality variables, job characteristics and organizational commitment amounted to 80.4% of the employee's performance. While the other was 19.6% for the variable outside the model describedKeywords: Personality, Job Characteristics, Employee Performance and Organizational Commitment